Exchangeability of the flagellin (FliC) and the cap protein (FliD) among different species in flagellar assembly1. Issue 1 (23rd October 2012) - Inaba, Satoshi; Hashimoto, Manami; Jyot, Jeevan; Aizawa, Shin‐Ichi
Abstract Flagellar filament self‐assembles from the component protein, flagellin or FliC, with the aid of the capping protein, HAP2 or FliD. Depending on the helical parameters of filaments, flagella from various species are divided into three groups, family I, II, and III. Each family coincides with the traditional classification of flagella, peritrichous flagella, polar flagella, and lateral flagella, respectively. To elucidate the physico‐chemical properties of flagellin to separate families, we chose family I flagella and family II flagella and examined how well the exchangeability of a combination of FliC and/or FliD from different families is kept in filament formation. FliC or FliD of Salmonella enterica serovar Typhimurium (Salty; family I) were exchanged with those of Escherichia coli (Escco; family I) or Pseudomonas aeruginosa (Pseae; family II). In a Salty fliC deletion mutant, Escco FliC formed short filaments, but Pseae FliC did not form filaments. In a Salty fliD deletion mutant, both Escco FliD and Pseae FliD allowed Salty FliC to polymerize into short filaments. In conclusion, FliC can be exchanged among the same family but not between different families, while FliD serves as the cap protein even in different families, confirming that FliC is essential for determining families, but FliD plays a subsidiary role in filament formation. © 2012 Wiley Periodicals, Inc.